The Association between Cerebrospinal Fluid Open Pressure and Body Mass Index in Idiopathic Intracranial Hypertension - Al-Khalidi, Hasanain A.; Goloom, Shehab A.; Radeef, Mohammed Radhi; Fahad, Ahmed Muhi (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Idiopathic intracranial hypertension (IIH) is strongly associated with obesity. However, the relationship between cerebrospinal fluid open pressure (CSFOP) and body mass index (BMI) is still controversial. AIM: The aim of this study is to assess the relationship between CSFOP and BMI in patients with IIH. METHODS: The measurement of CSFOP was done by Lumbar puncture manometry following a standardized procedure. Age and gender were registered and BMI was calculated for each patient. RESULTS: This study enrolled 104 patients with IIH, 96 females and eight males, with mean age was 31.88 ± 13.73 years. The mean CSFOP was 410.48 ± 129.98 mm H2O and the mean BMI was 33.97 ± 53 kg/m2. There was a significant positive relationship between the CSFOP and BMI (p = 0.0001) according to the Pearson correlation test. There was no relationship between the age (p = 0.06), gender (p = 0.16) and CSFOP of the patients. CONCLUSIONS: The CSFOP was positively correlated with high BMI of the patient. There was no relationship between patients demographic features and CSFOP.